2019
DOI: 10.1002/jimd.12049
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biogenic amines depletion and brain atrophy in adult patients with phenylketonuria

Abstract: Biogenic amines synthesis in phenylketonuria (PKU) patients with high phenylalanine (Phe) concentration is thought to be impaired due to inhibition of tyrosine and tryptophan hydroxylases and competition with amino acids at the blood-brain barrier. Dopamine and serotonin deficits might explain brain damage and progressive neuropsychiatric impairment in adult PKU patients. Ten early treated adult PKU patients (mean age 38.2 years) and 15 age-matched controls entered the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 35 publications
5
54
2
Order By: Relevance
“…For example, Bodner et al [ 34 ] reported ETPKU-related differences in putamen volume. Christ et al [ 36 ] documented decreased parietal and occipital GM volumes in a sample of individuals with ETPKU as compared to individuals without PKU. Most recently, Pilotto et al [ 36 ] found that higher CSF phe levels were correlated with GM atrophy in right parietal and bilateral frontal regions in a small sample of individuals with ETPKU.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bodner et al [ 34 ] reported ETPKU-related differences in putamen volume. Christ et al [ 36 ] documented decreased parietal and occipital GM volumes in a sample of individuals with ETPKU as compared to individuals without PKU. Most recently, Pilotto et al [ 36 ] found that higher CSF phe levels were correlated with GM atrophy in right parietal and bilateral frontal regions in a small sample of individuals with ETPKU.…”
Section: Discussionmentioning
confidence: 99%
“…40 A single study looked at the pathological hallmarks of AD, tau and amyloid, in the cerebrospinal fluid of 15 AwPKU (mean age 38.2 years), though, given the research targets and young age of participants, results are inconclusive. 41 There has been no study of tau, amyloid or synuclein in PKU, presumably as numbers of those studied at post mortem are small and tend to be younger. Huttenlocher 31 particularly raised the paucity of neuropathological study of the brain in AwPKU.…”
Section: Brain Healthmentioning
confidence: 99%
“…Separation was achieved in 5 min by applying isocratic elution (40% mobile phase A: 0.1% formic acid in MilliQ water and 60% mobile phase B: 100% methanol), at a flow rate of 0.6 mL/min and a column temperature of 40 • C. Detection was achieved using positive-ion electrospray ionization in multiple reaction monitoring mode, using the following transitions: m/z 295.2 > 235. 3…”
Section: Analysesmentioning
confidence: 99%
“…This leads to a diminished or sometimes even blocked conversion of Phe into tyrosine (Tyr). The resulting high Phe concentrations in blood and brain are detrimental for neurological development [3]. Therefore, the treatment of PKU and some other hyperphenylalaninemic disorders largely consists in dietary Phe restriction.…”
Section: Introductionmentioning
confidence: 99%